Challenges in Implementing Restorative Justice with Older Adults: Institutional Gatekeepers and Social Barriers. (12th March 2021) - Avieli, Hila; Band Winterstein, Tova; Gal, Tali
Abstract: Despite the consensus regarding the importance of restorative justice (RJ) as an alternative to the criminal justice system, some professionals and researchers have pointed out the challenges involved in its implementation with older adults who have been victimised. The aim of the present study was to explore the primary obstructions to implementing RJ intervention with older adults who have been victimised, as perceived by RJ facilitators, using the conceptual framework of social constructivism. An interpretive phenomenological analysis perspective was used to analyse the narratives of seven RJ facilitators, all of them highly experienced social workers. The narratives revealed three themes: the interpersonal and familial arena—the older person and his/her family as gatekeepers; the institutional arena—judicial and medical system personnel as gatekeepers; and the professional arena—RJ facilitators as gatekeepers. The findings suggest that some individuals and institutions maintain the conservative agenda of gatekeeping older adults to prevent them from encountering any danger. These findings indicate that, in keeping with the social work code of ethics, social workers need to consider older adults' right to self-determination in RJ contexts.